Membingkai Tanggungjawab Orang Tua dalam Mengembangkan Karakter Kristiani pada Anak - Hermanugerah, Prima; Legi, Hendrik; suyono, Suyono (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2022)
This research will briefly outline the things that support the formation of the character of children in Christian families who pay attention to the values of proper Christian faith teaching, namely the truth of God's word played by parents in a special environment. This article describes the role of parents in educating children according to Christian principles. The author analyzes several library sources, both books and journals, relating to the topic under discussion. Analysis of some literature shows that raising a child is a sacred mission given to parents. Parents have an important role to play in the education of mature Christians . Mental maturity prepares children for the challenges of the present. Parents also play a role in cultivating character and morals in children. This paper will briefly describe the things that support the formation of children's character in Christian families that pay attention to the values of proper Christian faith teaching, namely the truth of God's word played by parents in a special environment in the family (Formal In Education). AbstrakPenelitian ini akan menguraikan secara singkat tentang hal-hal yang menunjang pembentukan karakter anak dalam keluarga Kristen yang memperhatikan dari nilai-nilai pengajaran iman Kristen yang tepat yaitu kebenaran firman Tuhan yang diperankan oleh orang tua dalam lingkungan secara khusus. Artikel ini menjelaskan tentang peran orang tua dalam mendidik anak sesuai prinsip kristiani. Penulis menganalisis beberapa sumber perpustakaan, baik buku maupun jurnal, yang berkaitan dengan topik yang sedang dibahas. Analisis beberapa literatur menunjukkan bahwa membesarkan anak adalah misi suci yang diberikan kepada orang tua. Orang tua memiliki peran penting dalam pendidikan orang Kristen yang dewasa. Kematangan mental mempersiapkan anak menghadapi tantangan di masa kini. Orang tua juga berperan dalam menumbuhkan karakter dan moral pada anak. Tulisan ini akan menguraikan secara singkat tentang hal-hal yang menunjang pembentukan karakter anak dalam keluarga Kristen yang memperhatikan dari nilai-nilai pengajaran iman Kristen yang tepat yaitu kebenaran firman Tuhan yang diperankan oleh orang tua dalam lingkungan secara khusus di keluarga (Pendidikan In Formal).